2000
DOI: 10.1111/j.1528-1157.2000.tb00137.x
|View full text |Cite
|
Sign up to set email alerts
|

Moderators of the Effect of Preoperative Emotional Adjustment on Postoperative Depression After Surgery for Temporal Lobe Epilepsy

Abstract: Summary:Purpose: Other outcome measures besides seizure control must be considered when assessing the benefit of epilepsy surgery. We investigated the effect of preoperative psychosocial adjustment on postoperative depression in epilepsy patients followed up prospectively for 2 years after temporal lobectomy.Methods: The Washington Psychosocial Seizure Inventory (WPSI) evaluated psychosocial functioning; the Centre for Epidemiological Studies Depression Scale (CES-D) measured depression. Both were completed at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
31
0
4

Year Published

2005
2005
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(42 citation statements)
references
References 62 publications
7
31
0
4
Order By: Relevance
“…Depressive states and 'neuroticism' influence self-reported HRQOL, as predicted by cognitive theories of depression [33][34][35][36]. Self-report may therefore underestimate HRQOL in populations with a high prevalence of depression and neuroticism, such as epilepsy.…”
Section: Self-denigrationmentioning
confidence: 99%
“…Depressive states and 'neuroticism' influence self-reported HRQOL, as predicted by cognitive theories of depression [33][34][35][36]. Self-report may therefore underestimate HRQOL in populations with a high prevalence of depression and neuroticism, such as epilepsy.…”
Section: Self-denigrationmentioning
confidence: 99%
“…1,5,9,14) In contrast to the present results, some earlier studies identified poor seizure outcome and surgical side as strong predictive factors. 1,2,15) The findings of the types of postoperative disorders have also varied: earlier papers more commonly report milder psychiatric issues 9) and transient mood disorders such emotional lability and depression, 5) whereas we predominately observed conditions requiring treatment with antipsychotic drugs. The follow-up period and patient selection criteria might partly explain these discrepancies, as our subgroup of patients with postoperative psychiatric disorders was limited to patients who received psychotropic drugs 2 or more years after the surgery.…”
Section: Discussionmentioning
confidence: 97%
“…[1][2][3][4][5][6]9,11,[13][14][15]17,19) These problems have recently become a focus of interest, as intractable epilepsy is recognized as a chronic encephalopathy in which one seizure induces other seizures. 7) Therefore, we need to analyze the overall effects on the quality of life to demonstrate the benefits of surgery.…”
Section: Introductionmentioning
confidence: 99%
“…Postsurgical mortality has been considered in several recent reviews and meta-analyses with studies weighted to the assessment of temporal lobe resections [5 , [15][16][17]. Most studies suggest increased psychiatric morbidity postsurgically, although there are some reports to the contrary [18][19][20].…”
Section: Risk Profile For Suicide In Epilepsymentioning
confidence: 99%